The Influence of Financial Literacy, Fomo Behavior, Income and Self-Control on Generation Z's Personal Financial Planning in Palu City - Widi Y. Saleh; Jurana (Journal JEKAMI, 2026)
This study aims to analyze the effect of financial literacy, Fear of missing out (FoMO) behavior, income, and self-control on the personal financial planning of Generation Z in Palu. This research employs a quantitative approach, using primary data collected through online and offline questionnaires distributed to 100 Generation Z respondents residing in Palu. The sampling technique used is purposive sampling. The data were analyzed using SPSS version 25 through validity tests, reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing. The results of the study indicate that financial literacy, income, and self-control have a positive and significant effect on personal financial planning. Meanwhile, FoMO behavior does not have a significant effect on personal financial planning. Simultaneously, all four variables have a significant influence on the personal financial planning of Generation Z in Palu City. This research is expected to serve as a reference for future studies by considering other relevant variables such as lifestyle, social pressure, and digital literacy, or by adding a moderating variable.